Pojav resonance v prosto vrtečih se krožnih žagnih listih - Bučar, Bojan (Zbornik gozdarstva in lesarstva, 2003)
The article deals with the analysis of the aerodynamic excitation of a freely rotating circular saw blade. When the circular saw blade rotates freely, the air in the gullet spaces of the rim area of the tool separates (in the passing of the knife from its border flanking surfaces) and forms a variable waveform wake or turbulent airflow. The consequence of the time-variable turbulent airflow is the occurrence of variable air pressure along the knife surfaces, which constitutes the aerodynamic excitation of the saw blade. For the occurrence of transversal resonant vibration of the tool, there does not suffice only aerodynamically generated excitation force at a suitable frequency. In addition to the said condition, two additional conditions must also be met: the exciting pressure differences of the surrounding air must be adequately large, and the damping capabilities of the material of the saw plate sufficiently small. We have found that two or more natural manners of vibration are never excited simultaneously and that the transition from one resonant condition into another is abrupt. With the increasing frequency of rotation there is also, as a rule, an increase in the range of rotations in which the aerodynamic excitation of natural manners of vibration occurs.
Keywords: hrup; nihanje; resonanca; resonance; stabilnost; vzbujanje; žage; žagini listi